Commentary on the Old Testament ; v. 1 - Keil, Johan Karl Friedrich, 1807-1888; Delitzsch, Franz Julius, 1813-1890; Martin, James (Grand Rapids, MI Eerdmans)
Contents : v. 1 : The Pentateuch. Includes bibliographical references.
Reprinted 1981.
Keywords: Bible. O.T. -- commentaries